Engaging in a research interview: lifeworld-based learning through dialogue. Issue 5 (3rd September 2021) - Toft, Bente Skovsby; Lindberg, Elisabeth; Hörberg, Ulrica
ABSTRACT: Despite the common use of qualitative in-depth interviews in healthcare research, little empirical research exists on how dialogues about personal and sensitive topics affect the interviewees. This study aims to describe the meaning of participating in lifeworld-based research interviews conducted in a healthcare context experienced from the patients' perspective. The study has a hermeneutic-phenomenological approach. Eleven persons with severe obesity were purposefully recruited for repeated individual interviews about physical activity and lifestyle changes and asked about their experiences of being interviewed. The data underwent a hermeneutic text interpretation and a data-driven coding focusing on meaning. Ethical approvals were received. One main theme emerged: 'Lifeworld reflections are facilitated through the relationship with the researcher based on the sub-themes: 'Being interviewed is an occasion to stop, think and unfold one's narrative', 'Gaining insight can facilitate action and emotions' and 'It requires willingness to leave one's comfort zone'. Our conclusions are that a person's lifeworld experiences are important for being reflective, which can be both rewarding and hurtful for the interviewee. The research interview holds numerous ethical aspects, which must be considered to ensure the wellbeing of the interviewee.